(3MeGjI GdeeJdcGJ GdKbGajI CKfGA GdfRGY GdeSdM (B/ s - (3SjO QeVGf YHOGdHGbj ESeGYjds; (3CMeO CHhGdhaG eMeO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3efP CeO HYjO hGdfRGYGJ GdeSdMI JTcd NWkQG YXjkeG Ydi GdeeJdcGJ GdKbGajI(B: (3hbO MGhd GdeLJeY GdOhdj hVY fXGe bGfhfj dMeGjJgG(B: (3HGYJHGQgG JeKd edckG ddHTQjI LeYGA(B: (3hHJWhQ bhGYO GdbGfhf GdOhdj GdEfSGfj CUHMJ gfGc bhGYO JTcd LRAkG ef bhGYO GdbGfhf GdOhdj GdEfSGfj JgJe HGdeeJdcGJ GdKbGajI(B: (3hbO SHbJ GdTQjYI GdESdGejI Edi hVY fXGe bGfhfj eJcGed JYed fXeg HTcd eJSGfO jVef MeGjI aYGdI dgG(B.(3hfXQkG dCgejI GdehVhY aEffG fHMKg aj YOI CHhGH(B: (3GdHGH GdJegjOj(B: (3HMKfG ajg GdJYQja HeUWdMGJ GdOQGSI hGdJWhQ GdJGQjNj ddMeGjI(B: (3haj GdHGH GdChd(B: (3HMKfG aj eUGOQ GdMeGjI(B: (3haj GdHGH GdKGfj(B: (3HMKfG aj fWGb GdMeGjI(B: (3haj GdHGH GdKGdK(B: (3HMKfG aj CMcGe abOGf Ch JYdjb GdMeGjI(B: (3hJYQVfG aj GdHGH GdQGHY(B: (3dBdjGJ JWHjb CMcGe GdMeGjI(B: (3haj GdHGH GdNGeS(B: (3JWQbfG Edi GdeSFhdjI GdOhdjI GdeJQJHI Ydi GdGYJOGA Ydi GdeeJdcGJ GdKbGajI CKfGA GdfRGY GdeSdM(B: (3CeG GdHGH GdSGOS aJfGhdfG ajg GdGNJUGU GdbVGFj hGdJYGhf GdOhdj(B: (3Ke GdNGJeI hCge fJGFL GdHMK hGdJhUjGJ hGdebJQMGJs
(3jTJed Ydi edGMb(B: (3UaMI (B497-544s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2013s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B545-566s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GdeeJdcGJ GdKbGajIs; (3GdfRGY GdeSdMs; (3MeGjI GdeeJdcGJ GdKbGajIs; (3eUGOQ MeGjI GdeeJdcGJ GdKbGajI ai GdbGfhf GdOhdi s; (3fWGb JWHjb GdMeGjI s; (3GdjGJ JfajP GdMeGjg s; (3GdeSFhdjI GdOhdjgs; (3GdGNJUGU GdbVGFi s; (3bhGYO GdGNJUGU s; (3GdeSFhdjI GdOhdjg dGfJgGc MeGjg GdeeJdcGJ s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs